2011
DOI: 10.1111/j.1747-0080.2011.01513.x
|View full text |Cite
|
Sign up to set email alerts
|

nutritionDay: An Australian hospital's participation in international benchmarking on malnutrition

Abstract: Aim:  Malnutrition is a significant issue for hospitals worldwide. This project examined malnutrition prevalence and associated factors including meal consumption in an Australian hospital. Methods:  The cross‐sectional study was undertaken at a private hospital in Brisbane, Australia, for ‘nutritionDay in Europe’ 2009. Nutritional status (subjective global assessment), demographic, medical condition and intake data were collected from 147 inpatients across five medical specialties. Results:  The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…(14,17) However, the nutrition analysis identified that patient energy and protein intake continued to increase significantly over the day, with dinner being the highest contributor to dietary intake. The number of menu items selected at each main meal also didn't correlate with the dietary intake, suggesting that the menu items offered at lunch and dinner may be more nutrient dense than those at breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…(14,17) However, the nutrition analysis identified that patient energy and protein intake continued to increase significantly over the day, with dinner being the highest contributor to dietary intake. The number of menu items selected at each main meal also didn't correlate with the dietary intake, suggesting that the menu items offered at lunch and dinner may be more nutrient dense than those at breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have investigated nutrition care‐related practices amongst hospitalised patients in general (Elia et al ., ; Ferguson et al ., ; Agarwal et al ., ), none have focused on patients at risk of PU. Similarly, the nutritional intakes of hospitalised patients and factors that may affect these have been reported in Australian and international studies (Dupertuis et al ., ; Patel & Martin, ; Bauer et al ., ; Mudge et al ., ; Thibault et al ., ); however, there are no data available relating specifically to patients at risk of PU.…”
Section: Introductionmentioning
confidence: 98%
“…Although adequate food intake is essential for the clinical management of malnutrition, Kowanko et al 8 found that over one-third of patients in intensive care consume less than 50% of the calories provided by the standard hospital diet. In a recent study, Bauer et al 9 also found that approximately 50% of patients reported eating half or less of their meals, and these patients were four times more likely to be malnourished than patients who ate more than half of the meals.…”
Section: Introductionmentioning
confidence: 99%